2010
DOI: 10.1038/mp.2010.66
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in corticotropin-releasing factor receptor signaling and trafficking: potential role in female vulnerability to stress-related psychopathology

Abstract: Although the higher incidence of stress-related psychiatric disorders in females is well documented, its basis is unknown. Here we demonstrate that the receptor for corticotropin-releasing factor (CRF), the neuropeptide that orchestrates the stress response, signals and is trafficked differently in female rats in a manner that could result in a greater response and decreased adaptation to stressors. Most cellular responses to CRF in the brain are mediated by CRF receptor (CRFr) association with the GTP-binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
378
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(408 citation statements)
references
References 59 publications
27
378
2
1
Order By: Relevance
“…Crh secretion is sexually dimorphic (Bangasser and Valentino, 2012;Iwasaki-Sekino et al, 2009), and Crhr1 signaling is more sensitive in females as G-protein coupling is increased and receptor internalization is decreased compared to males (Bangasser et al, 2010). However, we show that gene expression of the selected candidate genes is independent of Crhr1.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Crh secretion is sexually dimorphic (Bangasser and Valentino, 2012;Iwasaki-Sekino et al, 2009), and Crhr1 signaling is more sensitive in females as G-protein coupling is increased and receptor internalization is decreased compared to males (Bangasser et al, 2010). However, we show that gene expression of the selected candidate genes is independent of Crhr1.…”
Section: Discussionmentioning
confidence: 65%
“…When acting through Crh receptor 1 (Crhr1), it mediates several of the rapid effects of acute stress in the hippocampus (Wang et al, 2013). Sex-differences in stress-induced gene regulation may therefore be due to differential responsiveness of the Crh system between sexes (Bangasser et al, 2010;Iwasaki-Sekino et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies provide more insight into the role for the CRF system in sex-linked differences in stress responses. Notably, a swim stress induces association of CRF receptors to β-arrestin2 and receptor internalization in male rats; in contrast, the same stressor decreases the ratio of cytoplasmic-to-total CRF receptor levels in female rats, suggesting CRF receptor recruitment to the plasma membrane and increased stress susceptibility (Bangasser et al, 2010). Thus, ovarian hormones and/or sex-linked differences in plasma membrane CRF receptor availability might underlie the loss of resilience to the final stress exposure observed herein in the opiatewithdrawn female, but not male, CRF 2 − / − mice.…”
Section: Summary Of the Resultsmentioning
confidence: 99%
“…We included Arrb2 based on the finding that in the locus coeruleus, female rats display lower levels of Arrb2, an important protein involved in the internalization of CRF-R1 receptors. 18,19 We recently presented a mechanistic hypothesis suggesting that nicotine withdrawal in females is mediated by an interaction between CRF, dopamine and estradiol systems in the NAcc. 11 Previous work has shown that dopamine levels are decreased in the NAcc during nicotine withdrawal.…”
Section: Original Investigationmentioning
confidence: 99%